(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study was carried out in 28 villages covering131 mango growers of three Upazilas in Chittagong District with view to examine the adoption status of BARI mango varieties at farmer’s level. The adoption status of improved mango varieties was unknown to the region. Results revealed that out of 11 varieties of BARI mango, the highest 77% farmers adopted BARI Aam-3 followed by BARI Aam- 4 (22.1%) and BARI Aam-8 15.9%. But the rate of adoption of other varieties of BARI Aam was found to be lower irrespective of all locations due to unavailability of sapling and unknown to the variety. The rate of adoption of individual production technologies of BARI mango varieties was found unsatisfactory. Majority of the farmers did not adopt recommended practices as stated in BARI Krishi Projokti Hathboi such as pit size, planting distance, application of manure and fertilizers, plant growth regulator, insects and diseases management. Farmers maintained pit size for mango sapling (1.4 ft × 1.4 ft× 1.3 ft) compared to recommended size of (3ft×3ft×3ft). Similarly, planting distance was 12.0 x11.7ft as against the recommended distance of 25ft×30ft. About 67.7% farmers adopted the improved practice such as breaking inflorescence of mango trees and 65.0% of farmers used mulching. But majority (52%) of farmers did not receive training and practice pruning for mango trees. Probit regression analysis revealed that yield of mango variety, training, extension contact, risk taking behavior and willingness to take loan has indeed helped in contributing to adopt BARI mango varieties significantly. Therefore, promoting training on BARI mango production technologies; ensuring the availability of BARI mango saplings, and campaigning about the varieties in mass media could help to increase the rate of adoption of BARI mango varieties in the region. Bangladesh J. Agril. Res. 43(2): 235-252, June 2018